2022
DOI: 10.1093/lifemeta/loac035
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as multifaceted regulators of ferroptosis

Abstract: Mitochondria are well known to be ‘energy factories’ of the cell as they provide intracellular ATP via oxidative phosphorylation. Interestingly, they also function as a ‘cellular suicidal weapon store’ by acting as a key mediator of various forms of regulated cell death, including apoptosis, pyroptosis, necroptosis and ferroptosis. Ferroptosis, distinct from the other types of regulated cell death, is characterized by iron-dependent lipid peroxidation and subsequent plasma membrane rupture. Growing evidence su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 181 publications
0
23
0
Order By: Relevance
“…These iron-sulphur clusters are essential cofactors in various cellular processes, including the TCA cycle, respiratory chain complexes, and cytoplasmic enzymes. Furthermore, mitochondria contain iron storage proteins similar to cytoplasmic ferritin, known as mitochondrial ferritin (FtMt), which interacts with NCOA4 to promote the release of iron from mitochondrial autophagy when iron levels in mitochondria are decreased [ 74 ].…”
Section: Iron Metabolismmentioning
confidence: 99%
“…These iron-sulphur clusters are essential cofactors in various cellular processes, including the TCA cycle, respiratory chain complexes, and cytoplasmic enzymes. Furthermore, mitochondria contain iron storage proteins similar to cytoplasmic ferritin, known as mitochondrial ferritin (FtMt), which interacts with NCOA4 to promote the release of iron from mitochondrial autophagy when iron levels in mitochondria are decreased [ 74 ].…”
Section: Iron Metabolismmentioning
confidence: 99%
“…The induction of ferroptosis with RAS selective lethal 3 (RSL3) resulted in modifications in the morphology of the mitochondria as well as the clustering of fragmented mitochondria around the nucleus ( Wang et al, 2020a ). In addition, the oxidation of lipids takes place on the plasma membrane and the membranes of various organelles with the inclusion of mitochondria ( Chen et al, 2021 ; Guo et al, 2022 ).…”
Section: Association Between Mitochondria and Ferroptosismentioning
confidence: 99%
“…Phospholipids, sterols, and sphingolipids make up the major constituents of the membrane lipids ( Klug and Daum, 2014 ). Phospholipids are naturally amphipathic, with a hydrophobic chain (constituted of a saturated or unsaturated fatty acyl group) at one end and a hydrophilic chain (containing phosphatidylethanolamine and phosphatidylcholine) at the other end, particularly the head ( Guo et al, 2022 ). Polyunsaturated fatty acids (PUFAs) are the preferential candidates for oxidative degradation during ferroptosis ( Rodencal and Dixon, 2023 ).…”
Section: Association Between Mitochondria and Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Studies have indicated that the excessive formation and accumulation of the reactive oxygen species (ROS) in mitochondria make cells prone to ferroptosis. [9][10][11][12] Ferroptosis is a type of programmed cell death, which is different from autophagy, necrosis, and apoptosis. It underlies the pathogenesis of a broad range of disorders, 13 such as cancer, anemia, and Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 99%